IMPLEMENTASI KEBIJAKAN PROGRAM ALAT MESIN PERTANIAN (ALSINTAN) DI DINAS TANAMAN PANGAN HORTIKULTURA DAN PERKEBUNAN PROVINSI BENGKULU BAGI KELOMPOK TANI DI PROVINSI BENGKULU - Iansyah, Habibie Asfa; Sakti, Budiman; Aprianty, Henny (UM. Bengkulu, 2025)
This study aims to analyze the implementation of the Alsintan program policy that has been implemented at the Bengkulu Provincial Horticultural and Plantation Food Crops Office and analyze the impact on farmer groups in the implementation of the Alsintan program policy, including human resource and technical factors in the field that affect the policy of the Alsintan program. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. The results of the study showed that the alsintan program in the horticultural and plantation food crops service was running well, both in terms of communication, resources, disposition and bureaucratic structure. However, the alsintan program still has a negative impact such as not being on target for the assistance provided and there are still many farmer groups that do not have technical capabilities in the operation of alsintan. Therefore, it is necessary to improve both in terms of communication, resources, disposition and bureaucratic structure, so that the alsintan program can continue to improve the quality of farmers in Indonesia. Keywords: program implementation, alsintan, farmer groups